Manajemen Pengembangan Kelembagaan di Pondok Pesantren (Studi Kasus di Asrama Unggulan Al-Mawarid Pondok Pesantren Tahfidzul Qur’an Nurul Falah Poncol Magetan) - Mufti Hanafi; Miftahul Huda (Excelencia: Journal of Islamic Education & Management, 2024)
This research is motivated by the increasing public interest in Islamic boarding schools. So that caretakers of Islamic Boarding Schools are required to continue to innovate in developing their institutions by making superior programs and increasingly adequate infrastructure at Islamic Boarding School Institutions. One of these institutional developments is the implementation of the Superior Dormitory which accommodates students who focus on memorizing the Koran. This research is a type of field research using a qualitative approach. Data collection techniques through interviews, observation and documentation. The purpose of this study was to find out the implementation of institutional development in the Al-Mawarid Excellence Dormitory at Tahfidzul Qur'an Islamic Boarding School Nurul Falah Poncol Magetan. Weaknesses and advantages of implementing institutional development in the Al-Mawarid Superior Dormitory and the Implications of institutional development in the Al-Mawarid Superior Dormitory for the recitation of the students. The findings obtained from this study are that in implementing institutional development at the Al-Mawarid Superior Dormitory, the management function of POAC (Planning, Organizing, Actuating, Controlling) or planning (objectives, teaching staff and costs) is organizing (halaqoh distribution according to students' memorization, extracurricular according to the talents and interests of the students) implementation (formal, non-formal and extracurricular learning) evaluation (quarterly meetings between administrators and caregivers and tests for increasing students' memorization ratings). The management of institutional development in the AlMawarid Featured hostel lacks social community and the advantages are 24-hour mentoring assistance and representative and complete dormitories. The implications of institutional development at the AlMawarid Featured Dormitory are the achievement of memorization of at least 5 juz 1 year, student achievements in academic and nonacademic as well as competitions at the district level and costs that are more expensive at this superior Dormitory because of the facilities and programs implemented.